Implementation of a Comprehensive Hepatitis C Virus (HCV) Treatment Program in Metro-Detroit. (4th October 2017) - Awali, Reda; Lohia, Prateek; Veltman, Jennifer; Cohn, Jonathan; Crane, Lawrence R
Abstract: Background: The newly introduced direct-acting antivirals (DAAs) for chronic hepatitis C virus (HCV) infection have substantially higher cure rates and less side effects compared with previous regimens. However, in order to achieve optimal patient engagement in HCV treatment, it's highly imperative to develop comprehensive HCV treatment programs which provide optimal services that help navigate patients through a challenging healthcare system. Methods: In 2014, a comprehensive HCV treatment program employing a multidisciplinary team service was created at our Ryan White sponsored clinic in Metro-Detroit. The team which included infectious disease physicians, nurse practitioners and social workers aimed at identifying and addressing the socioeconomic barriers among our underserved HCV-infected population. We present the characteristics of HCV patients enrolled in the program as well as assess the sustained viral response rates (SVR) among patients treated for HCV infection between October 2014 and January 2017. May 10, 2017 was the date of last recorded SVR for patients who completed their DAA treatment. Results: Up to May 10, 2017, the program included 317 patients with HCV infection. The mean age of patients was 59 years (SD = 8). Around 68% of the cohort were males and 89% were African Americans. Of 317 patients, 61 % had Medicaid only, 14% had Medicare only and 18% had Medicare and Medicaid. The 2 most common modes of HCV transmission among our cohort was IV drug use (60%) and male to male sex (11%). Most of the patients had genotype 1a (62%) and approximately 37% of them were co-infected with HIV. One-hundred and sixty patients (51%) received or started treatment with DAA; ledipasvir/sofosbuvir being the most commonly prescribed regimen (126/160; 79%). Among 109 HCV infected patients who were expected to finish their DAA treatment 12 weeks before the date of last recorded SVR, 107 (98%) completed treatment. SVR was achieved in 100 % of patients who completed their treatment. Conclusion: Despite the state Medicaid restrictions, the high DAA costs, and the challenging socioeconomic status of our population, our program was able to achieve impressive SVR rates comparable to other HCV management programs in the US. Disclosures: All authors: No reported disclosures.